Comparative safety profile of hyaluronic acid products for knee osteoarthritis: a systematic review and network meta-analysis. Issue 12 (December 2016) - Bannuru, R.R.; Osani, M.; Vaysbrot, E.E.; McAlindon, T.E.
Summary: Purpose: Intra-articular (IA) hyaluronic acid (HA) is considered a safer alternative to oral Non-Steroidal Antiinflammatory Drugs (NSAIDs) and opioids for knee osteoarthritis (OA). A recent review raised potential safety concerns about HA, warranting further review of safety outcomes. We examined the risks of HA compared with IA placebo and investigated whether the risks vary among individual HA preparations. Methods: We searched all relevant databases from inception to October 2015 and sought unpublished data. We included all knee OA trials which compared any of the 18 HA products and reported on adverse events (AEs) and withdrawals. We calculated odds ratios for safety data reported at the longest follow-up. Network meta-analysis was performed using a Bayesian hierarchical random effects model for mixed multiple treatment comparisons. Results: We identified 74 studies involving 13, 032 participants aged between 45 and 75 years. The proportion of women ranged from 28% to 100%. The overall incidence of local reactions reported across all products was 8.5%. Commonly reported AEs were transient local reactions, such as pain, swelling and arthralgia, which subsided rapidly. None of the HA products were statistically significantly different from IA placebo or from each other with regard to incidence of AEs. Three treatment-related serious adverse events (SAEs) were reported among 9214 participants. Conclusions: Given the very low incidence of any particular AEs, we conclude that HA products are relatively well tolerated. These products have a similar safety profile compared to each other. This information along with the comparative effectiveness profile and relative cost would be helpful for clinicians in delivering individualized patient care.